Empire's mistress, starring Isabel Rosario Cooper - Gonzalez, Vernadette Vicuña 1973- (Duke University Press, 2021)
"Empire's Mistress centers the life of Isabel Rosario Cooper, a mixed race vaudeville and film actor from the Philippines, notorious for being Douglas MacArthur's one-time mistress. Tracking her story through absences and traces in the archive, Gonzalez explores empire on the scale of the intimate. Cooper's itinerant life-from Manila, to Washington, D.C. and Los Angeles-is a rich text for understanding the mobilities and opportunities available to women like her in the first half of the twentieth century. Empire's Mistress wrests the story of Isabel Cooper away from the plot of the tragic Eurasian, while attending to the haunting legacies of race, sex, and empire that define her life, both onstage/onscreen, and off"--
Keywords: MacArthur, Douglas -- 1880-1964; Cooper, Elizabeth -- 1914-1960; Cooper, Isabel Rosario / 1914-1960; MacArthur, Douglas / 1880-1964 / Relations with women; Motion picture actors and actresses / Philippines / Manila / Biography; Filipino American women / Biography; MacArthur, Douglas / 1880-1964; Filipino American women; Motion picture actors and actresses; Relations with women; Philippines / Manila; Biographies; Biografie